Hematopoietic Cell Transplantation in Brazil: A National Benchmarking Study Focused on the Foundation for the Accreditation of Cellular Therapy (FACT) Performance Indicators - Simione, Anderson João; Silva, Cinthya; Vigorito, Afonso; Macedo, Antonio; Neves, Heliz; Sabaini, Paula; Ammi, Monique; Costa, Flavia; Cavilha, Adriana; Concilio, Rosana; et al. (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2025)
Systematic evaluation of hematopoietic cell transplantation (HCT) outcomes is essential to improve clinical practice and meet international quality standards. In Brazil, the partnership between the Brazilian Society of Cellular Therapy and Bone Marrow Transplantation (SBTMO) and the Center for International Blood and Marrow Transplant Research (CIBMTR) has advanced national data reporting and benchmarking through the Hematopoietic Cell Transplantation Brazilian Registry (HCTBR). This study reports outcomes from 11,210 first HCTs (5,984 allogeneic; 5,226 autologous) performed between 2012 and 2023 across 44 Brazilian centers. Median recipient age was 29 years for allogeneic and 53 years for autologous transplants. Acute leukemias predominated among allogeneic cases, while multiple myeloma was the most common indication for autologous HCT. Two-year overall survival was 82.0% for autologous and 59.8% for allogeneic transplants, with variation by donor type (matched related 61.8%, mismatched related 54.0%, unrelated 63.3%). Two-year non-relapse mortality was 8.0% and 21.6% for autologous and allogeneic transplants, respectively. The cumulative incidence of grade II–IV acute graft-versus-host disease (GVHD) at two years was 29.9%, with chronic GVHD incidence of 29.5%. Two-year relapse incidence was 24.1% for allogeneic and 25.8% for autologous HCT. Despite challenges within the Brazilian healthcare system, these outcomes align with international registry data. Adequate data completeness supports the robustness of these findings. Our results highlight the quality of Brazilian transplant programs and underscore the value of standardized outcome monitoring to foster continuous improvement. Strengthening center participation, follow-up, and data management remains critical to maintaining registry quality and enhancing patient care.